Mapping of Community Pharmacy Practices in Padangsidimpuan City - H, Cory, L F; W, Wiryanto; K, Khairunnisa (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: to find out the conditions of practice and mapping related to the category of community pharmacy practices in Padangsidimpuan City. Methods: The study was conducted by distributing assessment rubrics directly to 30 pharmacists in charge of pharmacies in the city of Padangsidimpuan. Data is the identity and choice of respondents for 2 or 3 descriptions of the level of compliance with each three-point scale; 0, 2 and 4 for each element. The level of fulfillment of standards consists of 7 categories based on cumulative points, and based on the average of points from each of the 5 standard aspects, including; professionalism, managerial, dispensing, pharmaceutical care, and public health services, depicted in spider web diagrams. This research was conducted in August - October 2019. Results: Mapping the results of the pharmacy practice category to 30 community pharmacy practices in Padangsidimpuan, among others: 8 pharmacies received excellent categories, 5 pharmacies of good categories, 3 pharmacies of adequate categories, 3 pharmacies of poor categories, 5 pharmacies of substandard categories, 5 pharmacies of the category not feasible, 1 category pharmacy is not very feasible.Conclusion: The average level of compliance with pharmacy practice standards in the city of Padangsidimpuan is included in the sub-standard category. Based on the average standard aspect points, professionalism has less categories, managerial has enough categories, dispensing enough categories, and pharmaceutical care is lacking categories and public health services have sub-standard categories.